IMPLICATIONS OF COMMUNITY SERVICE: FINANCIAL STATEMENT PRESENTATION TRAINING FOR ACCOUNTING MGMP TEACHERS TANGERANG CITY - Yessie, Afly; Indriawati, Fitri (Transpublika Publisher, 2024)
The purpose of this community service implication is to provide financial report presentation training for Tangerang City accounting MGMP teachers to increase knowledge and competency of financial accounting standards that apply in Indonesia. Implications of community service using direct experimental methods to determine the effectiveness of training. Collecting data through discussions and direct interviews to gain an understanding of teachers' perceptions and experiences. The results of this activity showed the success of increasing the knowledge and competence of teachers significantly. Teachers are more confident in teaching the presentation of financial reports in accordance with accounting standards applicable in Indonesia. An interactive and relevant teaching system provides broad knowledge and insight into the presentation of financial reports which is useful for teachers. Besides that, it improves practical skills that can be directly applied in teaching. The conclusion from the implications of this training, apart from increasing knowledge and competency for teachers, also contributes to improving the quality of accounting teaching and education in Tangerang City. The implications of training in presenting financial reports are very important to understand the use of accounting standards in Indonesia for industry.